Formal Modeling and Analysis of Timed Systems 10th International Conference, FORMATS 2012, London, UK, September 18-20, 2012, Proceedings - Jurdzinski, Marcin; Nickovic, Dejan (Theoretical Computer Science and General Issues, 2012)
This book constitutes the refereed proceedings of the 10th International Conference on Formal Modeling and Analysis of Timed Systems, FORMATS 2012, held in London, UK in September 2012. The 16 revised full papers presented together with 2 invited talks were carefully reviewed and selected from 34 submissions. The book covers topics of foundations and semantics, methods and tools, techniques, algorithms, hybrid automata, appilcations, real-time software and hardware circuits.